PEMBELAJARAN BAHASA ARAB MENGGUNAKAN BUKU DURUSULLUGHAH DENGAN METODE PROJECT BASED LEARNING DI PONDOK MEDERN ROUDHOTUL ILMI BAGKA - Khaikal Fasya Assefi; Wasilah; Jamanuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine and measure the effectiveness of Arabic language learning using the Durus al-Lughah textbook through the Project-Based Learning (PjBL) method at Pondok Modern Roudhotul Ilmi Bangka. The background of this research is based on the need to improve the conventional methods that have been predominantly used and tend to make students passive. The PjBL method is expected to create a more active, contextual, and communicative learning environment. This research employs a mixed-method approach, combining both qualitative and quantitative methods. Qualitative data were obtained through observation, interviews, and documentation, while quantitative data were collected through tests (pre-test and post-test) and questionnaires. The subjects of the study were all 28 seventh-grade students. The results of the study show that the implementation of the PjBL method significantly improved the students' Arabic learning outcomes. This is evidenced by the increase in the average pre-test score from 67.42 to 78.82 in the post-test. The paired sample t-test results showed a significance value of < 0.000, indicating a significant difference before and after the application of the PjBL method. Additionally, observations and interviews revealed that students became more active, motivated, and confident in using Arabic communicatively. Therefore, the Project-Based Learning method has proven to be effective in enhancing students’ Arabic language skills, especially when combined with the systematic material in the Durus al-Lughah textbook. This research is expected to serve as a reference for educators and Islamic educational institutions in developing more innovative and practical Arabic language learning strategies.